Intensity-dependent ultrafast dynamics of injection currents in unbiased GaAs quantum wells - Pochwała, Michał; Duc, Huynh Thanh; Förstner, Jens; Meier, Torsten (physica status solidi (RRL) - Rapid Research Letters)
The intensity dependence of optically-induced injection currents in unbiased GaAs semiconductor quantum wells grown in [110] direction is investigated theoretically for a number of well widths. Our microscopic analysis is based on a 14 x 14 band k . p method in combination with the multisubband semiconductor Bloch equations. An oscillatory dependence of the injection current transients as function of intensity and time is predicted and explained. It is demonstrated that optical excitations involving different subbands and Rabi flopping are responsible for this complex dynamics.
Keywords: tet_topic_qw

Oscillatory excitation energy dependence of injection currents in GaAs/AlGaAs quantum wells - Thanh Duc, Huynh; Förstner, Jens; Meier, Torsten; Priyadarshi, Shekhar; Racu, Ana Maria; Pierz, Klaus; Siegner, Uwe; Bieler, Mark (physica status solidi (c))
The injection of photocurrents by femtosecond laser pulses in (110)-orientedGaAs/AlGaAs quantum wells is investigated theoretically and experimentally. The roomtemperature measurements show an oscillatory dependence of the injection current amplitude and direction on the excitation photon energy. Microscopic calculations using the semiconductor Bloch equations that are set up on the basis of k.p band structure calculations provide a detailed understanding of the experimental findings.
Keywords: tet_topic_qw

Intensity dependence of optically-induced injection currents in semiconductor quantum wells - Pochwala, Michal; Duc, Huynh Thanh; Förstner, Jens; Meier, Torsten (CLEO:2011 - Laser Applications to Photonic Applications)
The intensity dependence of optically-induced injection currents in semiconductor quantum wells is investigated numerically. Oscillatory behavior of the electron charge current transients as function of intensity and time is predicted and explained.
Keywords: tet_topic_qw

Injection currents in (110)-oriented GaAs/AlGaAs quantum wells: recent progress in theory and experiment - Duc, H. T.; Pochwala, M.; Förstner, Jens; Meier, Torsten; Priyadarshi, S.; Racu, A. M.; Pierz, K.; Siegner, U.; Bieler, M. (Ultrafast Phenomena in Semiconductors and Nanostructure Materials XV)
We experimentally and theoretically investigate injection currents generated by femtosecond single-color circularly-polarized laser pulses in (110)-oriented GaAs quantum wells. The current measurements are performed by detecting the emitted Terahertz radiation at room temperature. The microscopic theory is based on a 14 x 14 k • p band-structure calculation in combination with the multi-subband semiconductor Bloch equations. For symmetric GaAs quantum wells grown in (110) direction, an oscillatory dependence of the injection currents on the exciting photon energy is obtained. The results of the microscopic theory are in good agreement with the measurements.
Keywords: tet_topic_qw

Electron g-factor anisotropy in symmetric (110)-oriented GaAs quantum wells - Hübner, J.; Kunz, S.; Oertel, S.; Schuh, D.; Pochwała, M.; Duc, H. T.; Förstner, Jens; Meier, Torsten; Oestreich, M. (Physical Review B)
We demonstrate by spin quantum beat spectroscopy that in undoped symmetric (110)-oriented GaAs/AlGaAs single quantum wells, even a symmetric spatial envelope wave function gives rise to an asymmetric in-plane electron Land´e g-factor. The anisotropy is neither a direct consequence of the asymmetric in-plane Dresselhaus splitting nor a direct consequence of the asymmetric Zeeman splitting of the hole bands, but rather it is a pure higher-order effect that exists as well for diamond-type lattices. The measurements for various well widths are very well described within 14 × 14 band k·p theory and illustrate that the electron spin is an excellent meter variable for mapping out the internal—otherwise hidden—symmetries in two-dimensional systems. Fourth-order perturbation theory yields an analytical expression for the strength of the g-factor anisotropy, providing a qualitative understanding of the observed effects.
Keywords: tet_topic_qw

Modeling excitonic line shapes in weakly disordered semiconductor nanostructures - Kuznetsova, I.; Gőgh, N.; Förstner, Jens; Meier, Torsten; Cundiff, S. T.; Varga, I.; Thomas, P. (Physical Review B)
Excitonic spectra of weakly disordered semiconductor heterostructures are simulated on the basis of a one-dimensional tight-binding model. The influence of the length scale of weak disorder in quantum wells on the redshift of the excitonic peak and its linewidth is studied. By calculating two-dimensional Fouriertransform spectra we are able to determine the contribution of disorder to inhomogeneous and also to homogeneous broadenings separately. This disorder-induced dephasing is related to a Fano-type coupling and leads to contributions to the homogeneous linewidth that depends on energy within the inhomogeneously broadened line. The model includes heavy- and light-hole excitons and yields smaller inhomogeneous broadening for the light-hole exciton if compared to the heavy-hole exciton, which agrees qualitatively with the experiment.
Keywords: tet_topic_qw

Reversal of Coherently Controlled Ultrafast Photocurrents by Band Mixing in Undoped GaAs Quantum Wells - Priyadarshi, S.; Racu, A. M.; Pierz, K.; Siegner, U.; Bieler, M.; Duc, H. T.; Förstner, Jens; Meier, Torsten (Physical Review Letters)
It is demonstrated that valence-band mixing in GaAs quantum wells tremendously modifies electronic transport. A coherent control scheme in which ultrafast currents are optically injected into undoped GaAs quantum wells upon excitation with femtosecond laser pulses is employed. An oscillatory dependence of the injection current amplitude and direction on the excitation photon energy is observed. A microscopic theoretical analysis shows that this current reversal is caused by the coupling of the light- and heavy-hole bands and that the hole currents dominate the overall current response. These surprising consequences of band mixing illuminate fundamental physics as they are unique for experiments which are able to monitor electronic transport resulting from carriers with relatively large momenta.
Keywords: tet_topic_qw

Microscopic analysis of charge and spin photocurrents injected by circularly polarized one-color laser pulses in GaAs quantum wells - Duc, Huynh Thanh; Förstner, Jens; Meier, Torsten (Physical Review B)
The dynamics of charge and spin injection currents excited by circularly polarized, one-color laser beams in semiconductor quantum wells is analyzed. Our microscopic approach is based on a 14x14 k · p band-structure theory in combination with multisubband semiconductor Bloch equations which allows a detailed analysis of the photogenerated carrier distributions and coherences in k space. Charge and spin injection currents are numerically calculated for [110]- and [001]-grown GaAs quantum wells including dc population contributions and ac contributions that arise from intersubband coherences. The dependencies of the injection currents on the excitation conditions, in particular, the photon energy are computed and discussed.
Keywords: tet_topic_qw

Microscopic theoretical analysis of optically generated injection currents in semiconductor quantum wells - Duc, Huynh Thanh; Förstner, Jens; Meier, Torsten (Ultrafast Phenomena in Semiconductors and Nanostructure Materials XIV)
A microscopic theory that describes injection currents in GaAs quantum wells is presented. 14 × 14 band k.p theory is used to compute the band structure including anisotropy and spin-orbit interaction. Transient injection currents are obtained via numerical solutions of the semiconductor Bloch equations. Depending on the growth direction of the considered quantum well system and the propagation and polarization directions of the incident light beam, it is possible to generate charge and/or spin photocurrents on ultrashort time scales. The dependence of the photocurrents on the excitation conditions is computed and discussed.
Keywords: tet_topic_qw

Generation of injection currents in (110)-oriented GaAs quantum wells: experimental observation and development of a microscopic theory - Bieler, M.; Pierz, K.; Siegner, U.; Dawson, P.; Duc, H. T.; Förstner, Jens; Meier, Torsten (Ultrafast Phenomena in Semiconductors and Nanostructure Materials XIII)
We have experimentally investigated injection currents generated by all-optical excitation of GaAs/AlGaAs quantum wells excited with 130 fs optical pulses. The currents have been detected via free-space THz experiments at room temperature. Our experiments prove that Coulomb effects strongly influence injection currents. This becomes most prominently visible when exciting light-hole exciton transitions. At this photon energy we observe a pronounced phase shift of the current transients which is due to oppositely oriented heavy-hole and light-hole type contributions. We are currently developing a microscopic theory based on a 14×14 k.p model in combination with the semiconductor Bloch equations to describe the observed features quantitatively. The combined theoretical and experimental approach will allow us to analyze the influence of the bandstructure and interaction effects on the injection current amplitude and current dynamics.
Keywords: tet_topic_qw

Transition between different coherent light–matter interaction regimes analyzed by phase-resolved pulse propagation - zu Siederdissen, Tilman Höner; Nielsen, Nils C.; Kuhl, Jürgen; Schaarschmidt, Martin; Förstner, Jens; Knorr, Andreas; Khitrova, Galina; Gibbs, Hyatt M.; Koch, Stephan W.; Giessen, Harald (Optics Letters)
We present phase-resolved pulse propagation measurements that allow us to fully describe the transition between several light–matter interaction regimes. The complete range from linear excitation to the breakdown of the photonic bandgap on to self-induced transmission and self-phase modulation is studied on a high-quality multiple-quantum-well Bragg structure. An improved fast-scanning cross-correlation frequency-resolved optical gating setup is applied to retrieve the pulse phase with an excellent signal-tonoise ratio. Calculations using the semiconductor Maxwell–Bloch equations show qualitative agreement with the experimental findings.
Keywords: tet_topic_polariton; tet_topic_qw

Ultrafast electron-phonon interaction of intersubband transitions: Quantum kinetics from adiabatic following to Rabi-oscillations - Butscher, Stefan; Förstner, Jens; Waldmüller, Inès; Knorr, Andreas (Physical Review B)
The interaction of electrons with LO phonons provides an important mechanism of optical dephasing and carrier scattering for the two-dimensional electron gas in semiconductor quantum wells. In this paper, the corresponding ultrafast nonlinearities for off-resonant and resonant intersubband excitations are investigated. Quantum kinetic effects of the electron-phonon interaction and the corresponding violation of the microscopic energy conservation yield a qualitative different picture compared to the standard Markovian theory, if the phonon energy is larger than the intersubband-gap energy.
Keywords: tet_topic_qw

Adiabatically driven electron dynamics in a resonant photonic band gap: Optical switching of a Bragg periodic semiconductor - Schaarschmidt, Martin; Förstner, Jens; Knorr, Andreas; Prineas, John P.; Nielsen, Nils C.; Kuhl, Jürgen; Khitrova, Galina; Gibbs, Hyatt M.; Giessen, Harald; Koch, Stephan W. (Physical Review B)
The adiabatic driving of the resonant electron dynamics in a one-dimensional resonant photonic band gap is proposed as an optical mechanism for nonlinear ultrafast switching. Pulsed excitation inside the photonic gap results in an ultrafast suppression and recovery of the gap. This behavior results from the adiabatic carrier dynamics due to rapid radiative damping inside the band gap.
Keywords: tet_topic_qw

Polaron signatures in the line shape of semiconductor ;intersubband transitions: quantum kinetics of the electron–phonon interaction - Butscher, S.; Förstner, Jens; Waldmüller, I.; Knorr, A. (physica status solidi (b))
We present a theory of the optical line shape of coherent intersubband transitions in a semiconductor quantum well, considering non-Markovian LO-phonon scattering as major broadening mechanism. We show that a quantum kinetic approach leads to additional polaron resonances and a resonance enhancement for gap energies close to the phonon energy.
Keywords: tet_topic_qw

Linear and nonlinear pulse propagation in a multiple-quantum-well photonic crystal - Nielsen, N. C.; Kuhl, J.; Schaarschmidt, M.; Förstner, Jens; Knorr, A.; Koch, S. W.; Khitrova, G.; Gibbs, H. M.; Giessen, H. (Physical Review B)
We investigate the temporal and spectral properties of subpicosecond pulses transmitted on the heavy-hole exciton transition through a multiple-quantum-well Bragg structure, exhibiting a one-dimensional photonic band gap. At low light intensities, a temporal propagation beating is observed. This beating is strongly dependent on the optical dephasing time T2 which is dominated by the radiative interwell coupling. In an intermediate intensity regime, the Pauli-blocking nonlinearity leads to gradual suppression of the photonic band gap and vanishing of the linear propagation beating. For highly nonlinear excitation, we find signatures of selfinduced transmission due to Rabi flopping and adiabatic following of the carrier density. Numerical simulations using the semiconductor Maxwell-Bloch equations are in excellent agreement with the experimental data up to intensities for which higher many-particle correlations become more important and self-phase modulation occurs in the sample substrate.
Keywords: tet_topic_qw

Nonlinear light pulse propagation in Bragg-periodic multiple semiconductor quantum well samples: ultrafast switching of a resonant photonic band gap - Schaarschmidt, Martin; Förstner, Jens; Knorr, Andreas; Prineas, John P.; Nielsen, Nils C.; Kuhl, Jürgen; Kithrova, Galina; Gibbs, Hyatt M.; Giessen, Harald; Koch, Stephan W. (Conference on Lasers and Electro-Optics/International Quantum Electronics Conference and Photonic Applications Systems Technologies)
We investigate theoretically the ultrafast nonlinear suppression of the resonant photonic band gap by strong laser pulses in semiconductor multiple qnantum wells. We achieve good agreement with our measurements on reflection samples.
Keywords: tet_topic_qw

Self-consistent Projection Operator Theory of Intersubband Absorbance in Semiconductor Quantum Wells - Waldmüller, Ines; Förstner, Jens; Knorr, Andreas (Nonequilibrium Physics at Short Time Scales)
Due to their many-particle character and their application in quantum cascade lasers, optical intersubband excitations in semiconductor quantum wells have become the focus of many recent publications [1,2]. In samples of high quality, intrinsic processes like electron-electron and electron-phonon many particle correlations determine the basic optical and transport properties such as lineshape and ultrafast dynamics. At the same time, intersubband excitations allow the direct investigation of dynamical properties of an important model system of many particle physics - the two-dimensional electron gas. We here present a microscopic theory for the intersubband dynamics and absorption. The calculation of absorption spectra of MQW systems is in principle composed of two parts: the determination of the polarization in a single quantum well within a density matrix approach as the source of electromagnetic radiation (Fig. 1a) and the calculation of the generated fields in the geometry of interest (Fig. 1b) within a Green's function approach [3,4]. We will here focus on the so-called single-pass geometry (cf. Fig. 1b, [5]).
Keywords: tet_topic_qw

Light Propagation and Many-Particle Effects in Semiconductor Nanostructures - Förstner, Jens
In dieser Arbeit wird eine Theorie vorgestellt, welche die quantenmechanische Vielteilchenphysik der Licht-Materie Wechselwirkung in Halbleiternanostrukturen beschreibt. Diese mikroskopische Beschreibung wird durch Kombination eines allgemeinen Dichtematrixansatzes mit speziellen Methoden zur Auswertung der Maxwellgleichungen wie der zeitaufgelösten Finite-Differenzen-Methode (FDTD) erreicht. Die Theorie wird auf verschiedene physikalische Situationen angewendet, wie z.B. Lichtausbreitung in Volumenhalbleitern, Interband- und Intersubbandübergänge in Quantenfilmstrukturen und optische Anregung von Quantenpunkten. Der Fokus liegt dabei auf der Beschreibung der linearen und nichtlinearen Antwort des Vielteilchensystems und seiner Ankopplung an das elektromagnetische Feld. In diesem Zusammenhang wird sowohl die Erzeugung als auch der Zerfall von optischen Anregungen untersucht, indem verschiedene Kopplungsmechanismen wie Elektron-Phonon-, Elektron-Photon- und Elektron-Elektron-Wechselwirkung berücksichtigt werden. Im Bereich der linearen Optik, also für Anregung mit geringer Intensität, ermöglicht die Theorie die Berechnung von Absorptionsspektren. Verschiedene Effekte in linearer Optik werden in dieser Arbeit untersucht und beschrieben: Linienaufspaltung durch Polaritonen im Volumenmaterial, Zunahme der Linienbreite bei Intersubbandübergängen verursacht durch Elektron-Elektron- und Elektron- Phonon-Streuung in einzelnen Quantenfilmen, Bildung einer optischen Bandlücke durch starke radiative Kopplung in Vielfilmstrukturen in Bragg-Geometrie, Phononenseitenbänder verursacht durch quantenkinetische Effekte in einzelnen Quantenpunkten und schliesslich Superradianz und Interferenzeffekte in Quantenpunktgittern. Bei nichtlinearer Anregung treten Dichte-Rabiflops als fundamentale Prozesse in allen betrachteten Systemen auf und können als kohärente Be- und Entvölkerung von quantenmechanischen Zuständen beobachtet werden. Der Einfluss von starker Lichtkopplung und verschiedenen Wechselwirkungen auf dynamische Größen wie die Besetzung wird untersucht. Bei nichtlinearer Propagation, bei der sich ein starker Lichtpuls über längere Strecken in einem System bewegt, wird selbstinduzierte Verstärkung der Transmission näher betrachtet. Des weiteren werden von der Coulombwechselwirkung verursachte nichtlineare Effekte wie exzitoninduziertes Dephasieren in Volumenmaterial und verschränkte Zustände in Quantenpunkten untersucht, die einen Zusammenbruch der Hartree-Fock- Näherung darstellen. Zusammenfassend werden in dieser Arbeit verschiedene lineare und nichtlineare optische Effekte in Halbleiternanostrukturen verschiedener Dimensionalität mit Hilfe einer allgemeinen Theorie, die einen Dichtematrixansatz mit den Maxwellschen Gleichungen kombiniert, untersucht.
Keywords: tet_topic_qd; tet_topic_qw; tet_topic_phc

Pulse propagation in Bragg-resonant multiple quantum wells: from pulse breakup to compression - Nielsen, N. C.; Kuhl, J.; Schaarschmidt, M.; Förstner, Jens; Knorr, A.; Koch, S. W.; Gibbs, H. M.; Khitrova, G.; Giessen, H. (physica status solidi (c))
The nonlinear propagation of subpicosecond pulses resonant to the hh 1s exciton in Bragg-periodic multiple quantum wells is investigated experimentally and theoretically. We show coherent pulse breakup and its suppression for increasing pulse intensity in good agreement with calculations based on the semiconductor Maxwell-Bloch equations. For highly nonlinear excitation, pulse compression is observed which is strongly enhanced by the additional contribution of self-phase modulation in the barrier and substrate material.
Keywords: tet_topic_qw

Theory of the lineshape of quantum well intersubband transitions: optical dephasing and light propagation effects - Waldmüller, Inès; Woerner, Michael; Förstner, Jens; Knorr, Andreas (physica status solidi (b))
We outline a theoretical description of the absorption linewidth of quantum well intersubband transitions by solving Maxwell’s equations for a non-local susceptibility including many particle effects. We show that the intersubband absorption results from a complex interplay between mean-field effects, dephasing contributions and light propagation effects, all being very sensitive to subband dispersion.
Keywords: tet_topic_qw

Correlated influence of carrier-carrier/carrier-phonon interaction and radiative damping on semiconductor intersubband transitions - Waldmuller, I.; Förstner, Jens; Knorr, A.; Woerner, M.; Reimann, K.; Kaindl, R.A.; Hey, R.; Ploog, K.H. (Postconference Digest Quantum Electronics and Laser Science, 2003. QELS.)
The linewidth of intersubband transitions resulting from simultaneous action of many-body contributions and radiative damping is analyzed. The processes are non-additive and a self-consistent treatment is necessary to explain recent experiments.
Keywords: tet_topic_qw

Theory of ultrafast dynamics and lineshape of semiconductor quantum well intersubband emitters - Waldmüller, Ines; Förstner, Jens; Knorr, Andreas (Nonlinear Optics: Materials, Fundamentals and Applications)
On the basis of a density matrix approach including electron-electron scattering, a detailed analysis of the temporal dynamics and the dephasing process after optical excitation in intersubband emitters is presented for a wide range of parameters.
Keywords: tet_topic_qw